Two complete mitochondrial genomes of Paraleucogobio fishes (Cypriniformes: Gobionidae) - Xia Zhang; Cuizhang Fu (Mitochondrial DNA. Part B. Resources, 2019)
Freshwater fishes in the genus Paraleucogobio include two species, Paraleucogobio notacanthus and Paraleucogobio strigatus. In this study, we determined complete mitochondrial genomes of P. notacanthus and P. strigatus to clarify their phylogenetic positions. The two mitochondrial genomes showed similar gene arrangements, codon use, gene overlaps or gene intervals with the length of 16,596 bp and 16,598 bp. Our phylogeny revealed that P. notacanthus and P. strigatus were nested within Gnathopogon fishes. The findings indicate that Paraleucogobio is a junior synonym of Gnathopogon.